Experiences of Hope for Youth Workers Engaging At-Risk and Street-Involved Young People: Applications to the Field of Counselling and Psychotherapy - Murdoch, Kenneth C.; Larsen, Denise (Canadian Journal of Counselling and Psychotherapy, 2018)
Working with at-risk youth can be rewarding, but it can sometimes become difficult to maintain hope. This study used basic interpretive inquiry to explore and understand the experience of hope for 4 youth workers at a community organization in a large Canadian city. The authors used thematic analysis to examine data from semi-structured interviews. Three categories were constructed from the data: nourishing the hopeful self, maintaining a culture of hope, and holding hopeful perspectives. Taken in tandem with extant literature on hope, a discussion of the findings reflects on provocative ideas related to the nature of hope and the self, as well as the place of hope at work. Implications for future research and practice are explored with a focus on promoting hope for helping professionals.